PENYULUHAN TENTANG ANEMIA BERDAMPAK EFEKTIF DALAM MENINGKATKAN PENGETAHUAN REMAJA DI LINGKUNGAN PONDOK PESANTREN - Alfiyana Yuliasari; Nirma Lidia Sari (WOMB Midwifery Journal, 2022)
The problem of anemia is still be a significant problem for young women, especially young women in Islamic boarding schools. Deficiency of nutritional intake and lack of health knowledge cause anemia to tend to be experienced by young women in Islamic boarding schools. This case is inversely proportional to the reality of young women who do not live in dormitories tend to be more aware of nutritional needs. This study aims to determine the effectiveness of counseling on knowledge about iron deficiency anemia in young women at the Pondok Pesantren Hafal Quran, Metro. The study used a quasi-experimental design method with a pre-post test design without control. The sample used for data collection techniques was accidental sampling, amounting to 11 people. The majority of teenagers who became respondents were late adolescents aged 17-20 years as much as 91% with high school education as much as 55%. The results showed that at pre-counseling, young women with moderate knowledge scores were 9 people (81.8%) and low was 2 people (18.2%). Meanwhile, post-counseling results showed that there were 9 teenagers with high knowledge (81.8%) and 2 people with moderate knowledge (18.2%). The Wilcoxon test showed that counseling about iron deficiency anemia was effective in increasing the understanding of adolescents at the Pondok Pesantren Hafal Quran Metro with a p-value 0.003. Thus, counseling activities have a significant impact on raising awareness of the importance of preventing anemia in young women at Islamic boarding schools.